Immunoelectron-microscopic localization of the 180 kD component of the neural cell adhesion molecule N-CAM in postsynaptic membranes - Persohn, Elke; Pollerberg, G. Elizabeth; Schachner, Melitta (The journal of comparative neurology, 1989)
In order to investigate the expression of cell adhesion molecules in synapses, we have studied the localization of the neural cell adhesion molecule N-CAM in the cerebellum and hippocampus of adult mice by immunocytological and immunochemical methods. Of the three molecular components of N-CAM with relative molecular masses (Mr) of 120, 140, and 180 kD, N-CAM 120 is not detectable in synaptosomal membranes, whereas N-CAM 140 is expressed on both pre- and postsynaptic membranes and N-CAM 180 is restricted to postsynaptic sites, with localization of the N-CAM 180-specific epitope in postsynaptic densities. Specificity of immunoreactivity is indicated by the observation that antibodies to the neural cell adhesion molecule L1 do not label synaptic membranes, whereas antibodies to two major components of postsynaptic densities, actin and erythrocyte spectrin, react with synaptic structures. Interestingly, N-CAM 180 is only detectable in subpopulations of synapses in the intact tissue. Isolated synaptosomes, opened for unimpeded accessibility of antibody by hypoosmotic treatment, also reveal a partial expression of N-CAM 180 in that 67% are labeled by antibodies to N-CAM 180, while antibodies to actin and erythrocyte spectrin react with 95% and 88% of all synaptosomes, respectively. N-CAM 180 does not appear to be differentially expressed in synapses of a particular morphological type, but is detectable in all types of synapses in the cerebellum and hippocampus, except for mossy fiber synapses and synapses between basket and Purkinje cells, which are generally N-CAM 180-negative. Since N-CAM 180 has been shown to be characteristic of stabilized or stabilizing cell contacts, possibly by its association with the cytoskeleton-membrane linker protein spectrin (Pollerberg et al.: J. Cell Biol. 101: 1921-1929, '85; Nature 324: 462-465, '86; Cell Tissue Res. 250: 227-236, '87), we would like to suggest N-CAM 180 plays an important role in determining the stability of contacts between pre- and postsynaptic membranes and state of synaptic activity.